Problematika Pengelolaan Usaha Mikro Kecil dan Menengah (UMKM ) untuk Meningkatkan Kesejahteraan Masyarakat di Kabupaten Langkat: Ditinjau dari Muqashid Syariah (el Buhuth: Borneo Journal of Islamic Studies, 2022)
This article discusses the problems of managing micro, small and medium enterprises to improve the welfare of the people who demand their existence. The purpose of this research is how the problems of managing MSMEs are to improve community welfare, how are the internal and external conditions of MSMEs, how is the urgency of handling them and what are the priority strategies of MSMEs. The method in this study uses a qualitative approach with SWOT analysis and the QSPM method. From the results of the SWOT analysis, it can be ascertained that micro, small and medium enterprises in Langkat district are in the status of a turn-around strategy. The meaning is to minimize weaknesses and seize opportunities. Currently, Langkat Regency MSMEs are indeed developing. The weakness comes from the MSME actors themselves while the opportunities come from outside opportunities and the QSPM matrix is generated from the SWOT matrix contained in the WO strategy. The alternative strategy that has the highest total attractiveness value is strategy number 4 with a TAS value of 5.566, namely Increasing self-competence SMEs about good financial management Keywords: Community Welfare, MSMEs, SWOT-QSPM